The impact of product characteristics of limited-edition shoes on perceived value, brand trust and purchase intention - Tri Minh Ha (Cogent Business & Management, 2021)
Individuals perceive that scarce goods are more costly than non-scarce goods and the nature and status of these products explains why scant products are more desirable. Limited-edition shoes (LES) are currently trendy among the younger generations in Vietnam and can be seen as a new marketing tool for Vietnamese sneaker brands to exploit. For such a motivation, we develop a theoretical model to study the product characteristics of LES and a purchase intention relying on uniqueness, psychological reactance and commodity theories. Specifically, our study examines the power of product characteristics of LES, including scarcity, uniqueness and self-expression, on social and economic values, brand trust and purchase intention. Our work adopts a questionnaire-based survey designed to gather data from 336 participants using convenience and snowball sampling techniques. Data collection focuses on young Vietnamese consumers with ages ranging from 18 up to and including 25. Our findings reveal that all product characteristics of LES are positively related to social and economic values, except self-expression and social value relationship. Additionally, social and economic values are confirmed to be significantly related to brand trust and purchase intention, although not between brand trust and purchase intention. Finally, our study offers theoretical contributions and practical implications.
Keywords: 650; brand trust; economic value; limited-edition shoes; purchase intention; scarcity; social value; uniqueness